Imagine a city that remembers : the Albuquerque rephotography project - Anella, Anthony; Childs, Mark C., 1959- (Querencias series., 2018)
This expanded and updated collection juxtaposes historic and contemporary photographs of Albuquerque to show diverse moments in the city's history and development.